The psychosocial impact of microtia and ear reconstruction: A national data-linkage study - Jovic, Thomas H.; Gibson, John A. G.; Jovic, Matthew; Dobbs, Thomas D.; Griffiths, Rowena; Akbari, Ashley; Whitaker, Iain S. (Frontiers in Pediatrics, 2023)
Introduction: Children with visible facial differences are believed to be at increased risk of negative psychosocial behaviours which may manifest as affective disorders. The aim of this study was to determine whether a diagnosis of microtia, and the associated surgical intervention, is associated with psychosocial implications including impaired educational attainment and a diagnosis of an affective disorder. Methods: A retrospective case-control study was conducted using data linkage to identify patients in Wales with a diagnosis of microtia. Matched controls were sought on the basis of age, gender and socioeconomic deprivation status to yield a total sample size of 709. incidence was calculated using annual and geographic birth rates. Surgical operation codes were used to classify patients into those that had no surgery, autologous reconstruction or prosthetic reconstruction. Educational attainment at 11 years of age, plus a diagnosis of depression or anxiety were used as markers of adverse psychosocial outcomes and the relative risk was attained using logistic regression analyses. Results: There were no significant associations between a diagnosis of microtia and an increased risk of adverse educational attainment or a risk of an affective disorder diagnosis. Male gender and higher deprivation scores were significantly associated with poorer educational attainment, irrespective of a diagnosis of microtia. Surgical intervention of any nature was also not associated with any increased risk of adverse educational or psychosocial outcomes in microtia patients. Discussion: Microtia patients in Wales do not appear to be at greater risk of developing affective disorders or impaired academic performance as a result of their diagnosis or associated surgical intervention. Whilst reassuring, the need for appropriate support mechanisms to maintain positive psychosocial wellbeing and academic achievement in this patient cohort is reinforced.